2007
DOI: 10.1017/s1930297500000577
|View full text |Cite
|
Sign up to set email alerts
|

Innumeracy and incentives: A ratio bias experiment

Abstract: The Ratio-Bias phenomenon, observed by psychologist Seymour Epstein and colleagues, is a systematic manifestation of irrationality. When offered a choice between two lotteries, individuals consistently choose the lottery with the greater number of potential successes, even when it offers a smaller probability of success. In the current study, we conduct experiments to confirm this phenomenon and test for the existence of Bias as distinct from general irrationality. Moreover, we examine the effect of introducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In relevant judgment studies, there have been many mixed results. Some studies did not find a positive effect of incentivization (Awasthi and Pratt, 1990;Baillon et al, 2022;Enke et al, 2023;Tversky and Kahneman, 1983;Wright and Anderson, 1989), while others demonstrated it (Charness et al, 2010;Dale et al, 2007;Enke et al, 2023;Epley and Gilovich, 2005;Lefebvre et al, 2011;Simmons et al, 2010;Wright and Aboul-Ezz, 1988, in different biases). To stray from anecdotes and cherry-picking, we mainly focus on meta-analyses of the literature.…”
Section: Bee 1 Incentivizationmentioning
confidence: 99%
“…In relevant judgment studies, there have been many mixed results. Some studies did not find a positive effect of incentivization (Awasthi and Pratt, 1990;Baillon et al, 2022;Enke et al, 2023;Tversky and Kahneman, 1983;Wright and Anderson, 1989), while others demonstrated it (Charness et al, 2010;Dale et al, 2007;Enke et al, 2023;Epley and Gilovich, 2005;Lefebvre et al, 2011;Simmons et al, 2010;Wright and Aboul-Ezz, 1988, in different biases). To stray from anecdotes and cherry-picking, we mainly focus on meta-analyses of the literature.…”
Section: Bee 1 Incentivizationmentioning
confidence: 99%